Development and Validation of the Masculine Attributes Questionnaire. (July 2017) - Cho, Junhan; Kogan, Steven M.
The present study describes the development and validation of the Masculine Attributes Questionnaire (MAQ). The purpose of this study was to develop a theoretically and empirically grounded measure of masculine attributes for sexual health research with African American young men. Consistent with Whitehead's theory, the MAQ items were hypothesized to comprise two components representing reputation-based and respect-based attributes. The sample included 505 African American men aged 19 to 22 years ( M = 20.29, SD = 1.10) living in resource-poor communities in the rural South. Convergent and discriminant validity of the MAQ were assessed by examining the associations of masculinity attributes with psychosocial factors. Criterion validity was assessed by examining the extent to which the MAQ subscales predicted sexual risk behavior outcomes. Consistent with study hypotheses, the MAQ was composed of (a) reputation-based attributes oriented toward sexual prowess, toughness, and authority-defying behavior and (b) respect-based attributes oriented toward economic independence, socially approved levels of hard work and education, and committed romantic relationships. Reputation-based attributes were associated positively with street code and negatively related to academic orientation, vocational engagement, and self-regulation, whereas respect-based attributes were associated positively with academic and vocational orientations and self-regulation. Finally, reputation-based attributes predicted sexual risk behaviors including concurrent sexual partnerships, multiple sexual partners, marijuana use, and incarceration, net of the influence of respect-based attributes. The development of the MAQ provides a new measure that permits systematic quantitative investigation of the associations between African American men's masculinity ideology and sexual risk behavior.